موت کا خوف: سیرت رسول ﷺ سے رہنمائی: A Guideline from Prophetic Tradition about Thanatophobia - Dr. Shaista Jabeen; Dr. Ayesha Tariq (Al Manhal Research Journal, 2023)
In this current era of science and technology, people are suffering through different phobias. These phobias are dragging them into a world of fear and uncertainty. One of these phobias, which is rapidly increasing is an intense fear of death or the dying process which is called “thanatophobia by psychologists. Basically thanatophobia is an anxiety disorder that can disrupt every human. Although it is natural to worry about death- whether it is yours or a loved one’s. For the people with thantophobia, feelings of worry and anxiety over dying are so intense that it impacts their ability to function day by day. Though death is unavoidable, it’s possible to overcome its fear. This article will deal with the prophetic way to overcome the fear of death. The sayings of the Holy Prophet PBUH related to death are a great relief for the persons going through this phobia. So we will seek help and guidance from Seerat tayyaba to get rid of this uncertainty.